2019
DOI: 10.1371/journal.pone.0210699
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between endorser social status and normative appeals on the endorsement effectiveness of pro-environmental behaviors

et al.

Abstract: Employing message endorser is a popular strategy in encouraging consumers to protect the environment. This research explores how the social status of endorsers and the forms of normative messages can influence the effectiveness of endorsement for pro-environmental behaviors. Drawing on the focus theory of normative conduct and the match-up hypothesis, the authors propose that the effects of endorser social status on consumers’ responses to green advertising are contingent on whether the normative messages is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(101 reference statements)
0
9
1
Order By: Relevance
“…Studies on exemplars have shown that exemplars can increase the positive effects of majority SNAs (Elgaaied-Gambier et al, 2018;He et al, 2019). More specifically, when promoting environmentally friendly behaviour, Elgaaied-Gambier et al (2018) showed that the presence of an exemplar in a message including a majority DSNA has a direct positive influence on the intention to purchase non-overpackaged products.…”
Section: Descriptive Social Norm Appealsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on exemplars have shown that exemplars can increase the positive effects of majority SNAs (Elgaaied-Gambier et al, 2018;He et al, 2019). More specifically, when promoting environmentally friendly behaviour, Elgaaied-Gambier et al (2018) showed that the presence of an exemplar in a message including a majority DSNA has a direct positive influence on the intention to purchase non-overpackaged products.…”
Section: Descriptive Social Norm Appealsmentioning
confidence: 99%
“…Overall, such SNAs are promising because they are subtle, low-cost, and effective in encouraging compliance (Rhodes et al, 2020;Yamin et al, 2019). Nevertheless, in the specific context of sustainable behaviour, there are very few studies combining the use of exemplars and SNAs, which do not use videos but printed information (Elgaaied-Gambier et al, 2018;He et al, 2019;Huber et al, 2018). However, Rhodes et al (2020) concluded that SNAs might be more effective in promoting sustainable behaviour when embedded in audio-visual material than in text-based stimuli.…”
Section: Exemplars and Social Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Content of advertising claims and appeals – Maximum research was found to be done on this topic. It included studies of types of appeals (Green and Peloza, 2014; Matthes et al , 2014; Jaeger and Weber, 2020), celebrity endorsements in green advertising (He et al , 2019) and use of text, color and visuals in green advertisements (Spack et al , 2012; Song and Luximon, 2019; Martinez et al , 2020).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Injunctive norms refer to the degree of social approval or disapproval of the act [ 28 ]. Through people’s perceptions, injunctive norms determine whether a particular behavior is socially acceptable or not [ 29 ]. Descriptive norms are based on a view of what other people usually do, providing information regarding what seems to be the most appropriate behavior [ 30 ].…”
Section: Introductionmentioning
confidence: 99%